Why and how users make choices in international dispute resolution: 2020 SIDRA Survey - Alexander, Nadja (Institutional Knowledge at Singapore Management University, 2020)
In this post on the Kluwer Mediation Blog, the experiences and views of legal and client users from common and civil law jurisdictions on why and how they choose dispute resolution mechanisms to resolve cross-border disputes are analysed.